Community Participation in the Village Forest Management Scheme in Oma village, Haruku Island District, Central Maluku Regency - Talaohu, Dendi Z; Tjoa, Marthina; Sahureka, Mersiana (Tropical Small Island Agriculture Management, 2024)
This research aims to look at the forms of community participation in Village Forest management in Oma village, Pulau Haruku District, Central Maluku Regency, the level of community participation in Village Forest management in Oma village, Pulau Haruku District, Central Maluku Regency, and to find out the factors that influence community participation in Village Forest Management in Oma village, Haruku Island District, Central Maluku Regency. The methods used in this research were qualitative and quantitative descriptive methods. The sample determination method uses purposive sampling or purposive sampling techniques. The data collection methods used in this research are observation, interviews, and literature study. Data analysis includes data reduction, data presentation, and conclusion. The level of community participation was analyzed using Likert scoring. Forms of community participation in the village forest program in Oma village, Haruku Island District, include thought, energy, and social involvement. The level of community participation in village forest management in Oma village in 4 stages of village forest management: the planning stage, namely, implementation, program evaluation, and utilization of results. The driving factor is synergy between stakeholders (central and regional government), the private sector, village government, and the community, and inhibiting factors include low human resources (HR). The level of community participation in village forest management in Oma village in the four stages of village forest management is included in the medium category. The driving factor in managing the Oma village forest is the synergy of stakeholders. While the inhibiting factor is the low quality of human resources (HR) in village communities.